Inspection and certification manual for sweetpotato planting material in Uganda - Ministry of Agriculture, Animal Industry and Fisheries, Uganda (2024)
In order to raise awareness, provide training, and technical assistance to crop inspectors, seed producers, laboratory operators, and screenhouse operators and field seed producers, the National Seed Certification Services (NSCS), Department of Crop Protection, Ministry of Agriculture, Animal Industry, and Fisheries (MAAIF), has created certification guidelines for sweetpotato planting material. In order to be eligible as a seed crop for vegetatively propagated crops, certified sweetpotato vines must fulfill the requirements of the Seeds Regulations. Tolerance thresholds for visual disease readings, pest incidence, seed crop varietal combinations, land use history, the source of planting material for the seed crop, and laboratory testing in the event of referral cases are the main pillars of the ministry's certification program. Consequently, standards and procedures for certification and inspection of sweetpotato planting material (seed) for all seed classes are included in these recommendations. It describes how to sample seed multiplication fields, how to determine the prevalence of pests and diseases that degrade seed quality, and how to present the findings. These guidelines guarantee that inspections are conducted accurately and impartially to assure the best quality of seed for production in the country.